Implementation of AI and VR at Pondok Pesantren Darul Ma'arif Rejang Lebong - Ari Yanto (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
Pesantren are traditional educational institutions in Indonesia that play a crucial role in shaping their students' character and religious knowledge. However, in this digital age, pesantren face the challenge of integrating technology into the learning process to remain relevant and effective. Technologies such as Artificial Intelligence (AI) and Virtual Reality (VR) offer significant opportunities to enhance the quality of education in pesantren. This study explores how AI and VR can be implemented at Pondok Pesantren Darul Ma'arif in Rejang Lebong and their impact on education. Using qualitative methods, this research analyzes the implementation of AI and VR in the pesantren, identifying the opportunities and challenges encountered. The findings show that the use of AI in personalizing learning materials and evaluations has increased the efficiency and effectiveness of education. AI helps teachers provide more personalized attention to students and automate administrative tasks. Meanwhile, using VR in Islamic history and jurisprudence classes offers a richer and more immersive learning experience. Students can